Quantum equilibration of the double-proton transfer in a model system porphine. Issue 39 (6th October 2020) - Albareda, Guillermo; Riera, Arnau; González, Miguel; Bofill, Josep Maria; Moreira, Iberio de P. R.; Valero, Rosendo; Tavernelli, Ivano
Abstract : The equilibration of the double proton transfer in porphine is demonstrated using a model system Hamiltonian. This highly coherent process could be witnessed experimentally using state-of-the-art femtosecond spectroscopy. Abstract : There is a renewed interest in the derivation of statistical mechanics from the dynamics of closed quantum systems. A central part of this program is to understand how closed quantum systems, i.e., in the absence of a thermal bath, initialized far-from-equilibrium can share a dynamics that is typical to the relaxation towards thermal equilibrium. Equilibration dynamics has been traditionally studied with a focus on the so-called quenches of large-scale many-body systems. We consider here the equilibration of a two-dimensional molecular model system describing the double proton transfer reaction in porphine. Using numerical simulations, we show that equilibration indeed takes place very rapidly (∼200 fs) for initial states induced by pump–dump laser pulse control with energies well above the synchronous barrier. The resulting equilibration state is characterized by a strong delocalization of the probability density of the protons that can be explained, mechanistically, as the result of (i) an initial state consisting of a large superposition of vibrational states, and (ii) the presence of a very effective dephasing mechanism.